The Relationship Between Soil Transmitted Helminthes (STH) Infection and Nutritional Status in Students of State Elementary School Number (SDN) 200 Palembang Indonesia - Chairil Anwar; Saraswati Annisa; Dalilah Dalilah; Novrikasari Novrikasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Infection of Soil Transmitted Helminthes (STH) is caused by intestinal nematodes where as in its life cycle, soil is needed as the media for the eggs or larvae to mature into effective forms, most commonly happen to children of school age. This infection is still one of the main problems in public health, including Indonesia. STH infection are widely distributed in tropical and subtropical areas. Lack of personal hygiene, poor environmental sanitation and low socioeconomic status are some factors that plays role in increasing the occurrence of the infection. This infection is also one of the causes responsible for malnutrition in children by decreasing appetite and food intake thus ensued adverse consequences such as declining growth pace, impairment of physical health, and weakening cognitive function. This study was conducted to analyze the association of STH infection with nutritional status of SDN 200 students in Kertapati District, Palembang. This study was an analytic observational research with a cross sectional research design. Samples consist of 107 students chosen using proportional stratified random sampling technique. Data was collected by direct interview using questionnaires, measuring body weight and height to obtain nutritional status which then classified using CDC 2000 growth curve while fecal contamination was examined using Kato Katz and modified Harada Mori methode in the Laboratory of Parasitology Medical Faculty of Universitas Sriwijaya. Data then analyzed using Chi-square test. From 107 students, 27.1% infection of STH was found on 29 students with 6 students (20.7%) infected by A. lumbricoides and 23 students (79.3%) infected by T. trichiura. Proportion of malnutrition status was found at 43.9%. Statistical test showed a significant association between STH infection and nutritional status (p=0.036; OR=3.167; Cl 95%: 1.163-15.237). There was a significant association between STH infection and nutritional status in students of SDN 200 Kelurahan Kemas Rindo Kertapati District Palembang City.